2020
DOI: 10.3390/jcm9082579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Administration of Somatostatin on Retinal Inflammation and Neurodegeneration in an Experimental Model of Diabetes

Abstract: Somatostatin (SST) is a neuroprotective peptide but little is known regarding the potential role of its anti-inflammatory effects on retinal neuroprotection. In a previous study, we provided the first evidence that topical (eye drops) administration of SST prevents retinal neurodegeneration in streptozotocin (STZ)-induced diabetic rats. However, STZ by itself could cause neurotoxicity, thus acting as a confounding factor. The aims of the present study were: (1) to test the effect of topical administration of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…This concept has broadened our understanding of the cells involved in the pathophysiology of DR and provided additional clues for developing novel therapies to prevent or halt the disease at the initial stage in comparison with current treatment modalities targeting on DME and proliferative DR at the advanced stage. A variety of novel treatment options focusing on the components of the neurovascular unit and their interactions, such as neurotrophic factors, antioxidants, anti-inflammatory agents, cell replacement and so on, have demonstrated protective effects on retinal functions and structure in both animal models and clinical [120,125,129] BDNF [121,130,131] Insulin & IGF-1 [122,134,138] SST [123,139] GLP-1 [124,143,[146][147][148] Anti-oxidants Flavonoids (Quercetin, Curcumin)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept has broadened our understanding of the cells involved in the pathophysiology of DR and provided additional clues for developing novel therapies to prevent or halt the disease at the initial stage in comparison with current treatment modalities targeting on DME and proliferative DR at the advanced stage. A variety of novel treatment options focusing on the components of the neurovascular unit and their interactions, such as neurotrophic factors, antioxidants, anti-inflammatory agents, cell replacement and so on, have demonstrated protective effects on retinal functions and structure in both animal models and clinical [120,125,129] BDNF [121,130,131] Insulin & IGF-1 [122,134,138] SST [123,139] GLP-1 [124,143,[146][147][148] Anti-oxidants Flavonoids (Quercetin, Curcumin)…”
Section: Discussionmentioning
confidence: 99%
“…Low SST level, an early event of DR, has been reported to stimulate apoptosis of neurons and glial activation in the retina through extracellular accumulation of glutamate and downregulation of glutamate transporter [ 82 , 123 ]. Therefore, SST has been applied to diabetic murine models via topical administration and found to ameliorate retinal neurodegeneration and gliosis by reducing glutamate excitotoxicity and inducible nitric oxide synthase (iNOS) level [ 123 , 139 ]. Furthermore, a multi-center, randomized controlled clinical trial (EUROCONDOR) has shown that topical administration of SST could stop worsening of pre-existing neuroretinal dysfunction, although no retinal neuroprotection was observed in subjects included in this clinical trial [ 140 ].…”
Section: Main Textmentioning
confidence: 99%
“…The main reasons why the systemic administration of SST analogs failed to arrest the progression of DR were recently reviewed [ 103 ]; one of the most important was their inability to cross the BRB. By contrast, topical administration of SST prevented retinal neurodegeneration and neurodysfunction assessed by ERG in streptozotocin (STZ)-induced diabetic rats [ 59 ] and in db/db mice [ 104 ]. The main mechanisms were: (a) anti-inflammatory action; (b) anti-apoptotic activity, thus preventing the misbalance between pro-apoptotic and survival signaling; and (c) the inhibition of diabetes-induced glutamate–aspartate transporter (GLAST) downregulation (an essential molecule for the clearance of glutamate), thus preventing the glutamate accumulation in the retina induced by diabetes [ 59 , 104 , 105 ].…”
Section: Treatment Based On Neuroprotectionmentioning
confidence: 99%
“…By contrast, topical administration of SST prevented retinal neurodegeneration and neurodysfunction assessed by ERG in streptozotocin (STZ)-induced diabetic rats [ 59 ] and in db/db mice [ 104 ]. The main mechanisms were: (a) anti-inflammatory action; (b) anti-apoptotic activity, thus preventing the misbalance between pro-apoptotic and survival signaling; and (c) the inhibition of diabetes-induced glutamate–aspartate transporter (GLAST) downregulation (an essential molecule for the clearance of glutamate), thus preventing the glutamate accumulation in the retina induced by diabetes [ 59 , 104 , 105 ]. This pre-clinical evidence lead to the implementation by the European Consortium for the Early Treatment of Diabetic Retinopathy (EUROCONDOR) of the first phase II-III clinical trial using neuroroprotective drugs for treating early stages of DR in type 2 diabetes.…”
Section: Treatment Based On Neuroprotectionmentioning
confidence: 99%
“…Targeting somatostatin receptors as novel analgesic and anti-inflammatory drug developmental approaches has emerged after our team discovered that somatostatin was released from the activated capsaicin-sensitive peptidergic sensory nerve endings into the systemic circulation which leads to anti-inflammatory and anti-hyperalgesic actions at distant parts of the body ( Pintér et al, 2006 ; Szolcsanyi et al, 2011 ; Pintér et al, 2014 ; Schuelert et al, 2015 ; Shenoy et al, 2018 ; Hernández et al, 2020 ; Kuo et al, 2020 ). These effects were mimicked by a synthetic heptapeptide agonist, TT-232, acting on the somatostatin receptors subtype 4 and 1 (SST 4 and SST 1 ) located on both primary sensory neurons and immune cells ( Pintér et al, 2002 ; Helyes et al, 2004 ; Szolcsányi et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%